18/24 can both be divided by 6, so it's 3/4
Answer:
Step-by-step explanation:
G (x) = x + 1 (fog) (x) = x 2 + 3x + 1 ⇒ (fog) (x) = x 2 + 3x + 1 ⇒ f (g (x)) = x 2 + 3x + 1 ⇒ f (x + 1) = x 2 + 3x + 1 Eg x + 1 = p, then x = p - 1. ⇒ f (p) = (p - 1) 2 + 3 ( p - 1) + 1 ⇒ f (p) = p 2 - 2p + 1 + 3p - 3 + 1 ⇒ f (p) = p 2 + p - 1 So f (x) = x 2 + x - 1 - ->
ANSWER IS : x 2 + x - 1
Answer:
y= 4x+8
Step-by-step explanation:
Add 12x to both sides.
3y=24+12x
The equation is in standard form.
3y=12x+24
Divide both sides by 3.
3
3y
=
3
12x+24
Dividing by 3 undoes the multiplication by 3.
y=
3
12x+24
Divide 24+12x by 3.
y=4x+8